Spermatozoa Quality of Etawah Crossbreeds in Tris Egg Yolk Diluent and Addition of Purple Sweet Potato Extract - Syahdan, Roshif; Muhammad Riyadhi, Muhammad Riyadhi; Herliani, Herliani (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
This study aimed to determine the effect of using tris diluent with purple sweet potato extract added as a diluent and its effect on maintaining the motility and viability of spermatozoa of Etawah crossbreed goats. Semen was collected using an artificial vaginal method and evaluated macroscopically and microscopically. The study used a completely randomized design (CRD) with four treatments and five replications consisting of 80% tris + 20% egg yolk as control (P0), 79% tris + 20% egg yolk + 1% purple sweet potato extract (P1). , tris 77% + egg yolk 20% + purple sweet potato extract 3% (P2), tris 75% + egg yolk 20% + purple sweet potato extract 5% (P3), tris 73% + egg yolk 20% + purple sweet potato extract 7% (P4). Semen was preserved and evaluated for motility and viability every 24 hours and stored at 3-5℃ until motility was at least 40%. The characteristics of fresh Etawah crossbreed goat semen were volume 1 ml, concentration 5.553 million/ml, motility 80%, viability 85.5%, and abnormality 4.7%. The results of the motility and viability of semen preservation after treatment on the third day in a row showed that P1 (55,0%; 67,5%) was significantly higher (P